2019
DOI: 10.48550/arxiv.1910.04781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stochastic Gravitational Wave Background from Global Cosmic Strings

Chia-Feng Chang,
Yanou Cui

Abstract: Global cosmic strings are generically predicted in particle physics beyond the Standard Model, e.g., a post-inflationary global U (1) symmetry breaking which may associate with axion-like dark matter. We demonstrate that although subdominant to Goldstone emission, gravitational waves (GWs) radiated from global strings can be observable with current/future GW detectors. The frequency spectrum of such GWs is also shown to be a powerful tool to probe the Hubble expansion rate of the Universe at times prior to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Further phenomenological consequences for both QCD axion and general ALPs are worth further exploration. Meanwhile a caveat for the scenario of post-inflationary PQ-breaking is that, as in conventional misalignment, topological defects' contribution to the axion relic density may dominate over the misalignment contribution, and is worth revisiting to advance and complete our understanding of the axion production mechanism [14,17,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Further phenomenological consequences for both QCD axion and general ALPs are worth further exploration. Meanwhile a caveat for the scenario of post-inflationary PQ-breaking is that, as in conventional misalignment, topological defects' contribution to the axion relic density may dominate over the misalignment contribution, and is worth revisiting to advance and complete our understanding of the axion production mechanism [14,17,20,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detection of a cosmogenic SGWB can potentially address many long-standing questions in particle physics and cosmology (e.g. [19][20][21][22][23][24][25][26][27][28][29][30][31]), and allows us to probe very early stages of the Universe.…”
mentioning
confidence: 99%
“…Very recently, inspired by its intimate connections to axion dark matter physics, significant progress has been made in simulating global topological defects and on the GW signals originated from it [42][43][44][45][46]. With a semianalytical approach based on the Velocity-dependent One-Scale (VOS) model, our earlier work [24] demonstrated that the GW signal from global strings, albeit notably smaller than that from its NG string counterpart, can be within reach of future GW experiments such as LISA [6,7], AEDGE [47], DECIGO and BBO [48]. Such a positive prospect of detection has been confirmed by simulation-based work [45,46], although details differ which will be addressed in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A weak logarithmic time-dependence of the tension is common for global cosmic strings. See[10] and references therein 2. The former option with µ ∼ H 2 has been considered in Ref [11]…”
mentioning
confidence: 99%